(untitled) (Tempo e Argumento, 2016)
The violence perpetrated by some Islamic fundamentalist groups in recent years, particularly the murder of the French cartoonists who worked for Charlie Hebdo, in early 2015, bring up doubts in the Western societies regarding the nature of their economic system, their global interconnection, the democracy, and specifically the freedoms. This article analyzes some cartoons of Muhammad published by the Danish newspaper Jyllands-Posten, in 2005, and by the French newspaper Charlie Hebdo, in 2012, and it explores their humor, their violence, and the reactions raised by them. The brief reflections derived from the analysis of these cases lead us to a discussion about the ‘Western’ tradition of satire, addressing religious freedom and freedom of expression, in addition to the very idea of democracy. Theories proposed by classic authors, such as Montesquieu and Stuart Mill, as well as those by contemporary authors who thought of the democratic freedoms, such as John Rawls and Pierre Rosanvallon are addressed, situating this relevant debate of contemporaneity in the long-term. This short essay promotes the debate about the limits of humor, especially in its relation to religions and politics nowadays. Keywords: Humor; Liberty; Democracy; Cartoon; Muhammad.